Improving antitumor targeting via using PL3 homing peptide and cell-penetrating peptide Authors - Dhafir Masheta; Shafq Al-Azzawi (Belgorod National Research University, 2023)
Introduction: Tumor-homing peptides have gained great attention as tools for the development of non-invasive and targeting drug delivery systems (DDS) to minimize drug systemic toxicity and enhance bioavailability. This study aims to improve antitumor targeting in prostate cancer via uploading a drug to a DDS comprised of a cell penetrating peptide decorated with a tumor-homing peptide, PL3. Material and Methods: The DDS was constructed via solid-phase peptide synthesis and then characterized via mass spectrum and high performance liquid chromatography. A cell viability assessment to evaluate its cytotoxicity on both tumor (prostate cancer cells) and normal cells was conducted, while a confocal laser scanning microscope and flow-cytometer were employed to investigate internalization. To inspect the effectiveness of the drug-loaded DDS, a biochemical enzyme inhibition assay on the target enzyme dihydrofolate reductase (DHFR) was performed. ‎ Results and Discussion:‏ The findings supported the succeeded synthesis and loading of the drug into this carrier system and demonstrated its high efficacy in cytotoxic effect and inhibiting DHFR with considerable cellular uptake in prostate cancer cells. Conclusion: The drug was delivered to the target prostate cancer cells by the PL3-functionalized DDS, limiting its localization to tumor cells rather than normal cells. Therefore, the study results highlighted the significance of the DDS in tumor therapy interventions.